ANALYSIS OF COSTS-RETURNS PROFITABILITY IN GROUNDNUT MARKETING IN BEKWARRA LOCAL GOVERNMENT AREA CROSS RIVER STATE, NIGERIA - I. B. Adinya (Journal of Animal and Plant Sciences, 2009)
This study examined costs-returns profitability in groundnut marketing in Bekwarra Local Government Area, Cross River State, Nigeria. Data were obtained from a random sample of 120 respondents in the study area by means of structured questionnaire. Data collected were analyzed using descriptive statistics and costs-returns analysis. Results from the analysis revealed that a net return of N1, 250.00 was realized with N0.22 made on every naira invested. Groundnut marketing is a profitable business, with attractive net return on investment. This study shows that groundnut marketers are faced with several constraints in their marketing activities. These constraints negatively affect the efficiency of groundnut marketing in the study area. Notable among them are high cost of transportation, lack of capital, lack of extension services, lack of price information, poor market infrastructures, inaccessibility of formal credit source because of high interest rate and lack of roads maintenance/bad roads occupied 15%, 14.17%, 11.67%, 10%, 9.17%, 9.17% and 8.33% respectively. For efficient marketing of groundnut in the study area, these constraints must be drastically reduced to the barest minimum. This can be done through efficient policy formulation and implementation, proper supervision of groundnut marketing programme, effective extension services and proper agricultural financing. It would pave a way to increase profit and will help alleviate poverty in Cross River State. It is also recommended that groundnut marketers in the study area should form cooperative group(s) to have access to loans from bank(s) for letter capital base for higher output.
Keywords: Economic Analysis; Costs-Returns; Groundnut; Marketing; Profitability.